Protein glycosylation: a promising way to modify the functional properties and extend the application in food system. Issue 15 (22nd August 2019) - Zhang, Qing; Li, Lin; Lan, Qiuyu; Li, Meili; Wu, Dingtao; Chen, Hong; Liu, Yaowen; Lin, Derong; Qin, Wen; Zhang, Zhiqing; Liu, Jiang; Yang, Wenyu
Abstract: Modification of functional properties by glycosylating with polysaccharides is an effective solution to improve the internal disadvantages of native proteins. Generally, protein glycosylation belongs to the first stage of the Maillard reaction in essence. Dry-heating, wet-heating, and their combination are the major methods for the preparation of protein-polysaccharide conjugates (PPC). Spectrophotometry, spectroscopy, electrophoresis, calorimetry, chromatography, and mass spectrometry are confirmed to be the most effective methods for the identification of PPC. After glycosylation, functionalities of the native protein, including solubility, rheological properties, emulsifying properties, foaming properties, gel property, film-forming properties, thermal stability, antioxidant activity, allergenicity, and antibacterial properties, are improved. The PPC is extensively used as an encapsulation or a delivering material in order to improve the bioaccessibility of bioactive compounds in food system. Some new applications in food processing could be explored using PPC as an ingredient based on the improved functional properties, such as 3-dimensional printing food, gelled food, and colloid food. Furthermore, the model of protein glycosylation and the application of PPC in food processing could be extended to other protein modification to broaden the exploitation of native protein resource for the processing of novel foods.